Insights into early evolutionary adaptations of the Akkermansia genus to the vertebrate gut - González, Dámariz; Morales-Olavarria, Mauricio; Vidal-Veuthey, Boris; Cárdenas, Juan P. (Frontiers in Microbiology, 2023)
Akkermansia, a relevant mucin degrader from the vertebrate gut microbiota, is a member of the deeply branched Verrucomicrobiota, as well as the only known member of this phylum to be described as inhabitants of the gut. Only a few Akkermansia species have been officially described so far, although there is genomic evidence addressing the existence of more species-level variants for this genus. This niche specialization makes Akkermansia an interesting model for studying the evolution of microorganisms to their adaptation to the gastrointestinal tract environment, including which kind of functions were gained when the Akkermansia genus originated or how the evolutionary pressure functions over those genes.In order to gain more insight into Akkermansia adaptations to the gastrointestinal tract niche, we performed a phylogenomic analysis of 367 high-quality Akkermansia isolates and metagenomeassembled genomes, in addition to other members of Verrucomicrobiota. This work was focused on three aspects: the definition of Akkermansia genomic species clusters and the calculation and functional characterization of the pangenome for the most represented species; the evolutionary relationship between Akkermansia and their closest relatives from Verrucomicrobiota, defining the gene families which were gained or lost during the emergence of the last Akkermansia common ancestor (LAkkCA) and; the evaluation of the evolutionary pressure metrics for each relevant gene family of main Akkermansia species. This analysis found 25 Akkermansia genomic species clusters distributed in two main clades, divergent from their non-Akkermansia relatives. Pangenome analyses suggest that Akkermansia species have open pangenomes, and the gene gain/loss model indicates that genes associated with mucin degradation (both glycoside hydrolases and peptidases), (micro)aerobic metabolism, surface interaction, and adhesion were part of LAkkCA. Specifically, mucin degradation is a very ancestral innovation involved in the origin of Akkermansia. Horizontal gene transfer detection suggests that Akkermansia could receive genes mostly from unknown sources or from other Gram-negative gut bacteria. Evolutionary metrics suggest that Akkemansia species evolved differently, and even some conserved genes suffered different evolutionary pressures among clades. These results suggest a complex evolutionary landscape of the genus and indicate that mucin degradation could be an essential feature in Akkermansia evolution as a symbiotic species.